Modelling a bright z = 6 galaxy at the faint end of the AGN luminosity function. Issue 3 (20th April 2020) - Trebitsch, Maxime; Volonteri, Marta; Dubois, Yohan
ABSTRACT: Recent deep surveys have unravelled a population of faint active galactic nuclei (AGNs) in the high-redshift Universe, leading to various discussions on their nature and their role during the Epoch of Reionization. We use cosmological radiation hydrodynamics simulations of a bright galaxy at z ∼ 6 (${M_\star } \gtrsim 10^{10}\, {\rm M}_{\odot }$ ) hosting an actively growing supermassive black hole to study the properties of these objects. In particular, we study how the black hole and the galaxy coevolve and what is the relative contribution of the AGNs and of the stellar populations to the luminosity budget of the system. We find that the feedback from the AGN has no strong effect on the properties of the galaxy, and does not increase the total ionizing luminosity of the host. The average escape fraction of our galaxy is around $f_{\rm esc} \sim 5{{\ \rm per\ cent}}$ . While our galaxy would be selected as an AGN in deep X-ray surveys, most of the ultraviolet (UV) luminosity is originating from stellar populations. This confirms that there is a transition in the galaxy population from star-forming galaxies to quasar hosts, with bright Lyman-break galaxies with M UV around −22 falling in the overlap region. Our results also suggest that faint AGNs do not contribute significantly to reionizing the Universe.